Analisis Penerjemahan Teks Eksposisi Pada Artikel Yang Berjudul Depression - Setyawardani, Wilis; Meri Dewi Pendit, Ni Putu (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
Translation is the process of switching the source text (Tsu) to the target text (TSa) commensurately so that it can be understood by the reader. This study aims to convey the information contained in the source text (TSu) or in this study used exposition texts and explain methods and techniques of translation to Indonesian. An exposition text is a text that outlines information. The method used in this study is a descriptive qualitative research method. The object used in this study is an article entitled Depression. The results show that the article entitled Depression has a written language style. Some of the translation methods used in the article include faithful and communicative methods. In addition, several translation techniques are also used, including transposition, amplification, natural borrowing, pure borrowing, literal, reduction, description, and kalke techniques. Through the translation methods and techniques used in the translation, a reading text that is easier to understand is produced, does not change the style of the original language, even though the translation results are not perfect.